Treatment of Brachial Plexus Injuries (IntechOpen, 2023)
Despite immense advancements, brachial plexus injuries continue to be an area where improvement is much needed. While some problems have been solved, there remain difficult situations where patients desperately need the neurosurgeon's help. This book is an attempt to put the state of the art in some of these less known areas, to provide the reader with an insight into what is currently being done today and what might be the possible therapeutic strategies for the future. We attempt not only to provide information but also more importantly to awake the interest of as many researchers as possible to find new solutions to old problems.